Extreme maternal morbidity: gynecological and obstetrical admissions to general hospital intensive care units - Acho Mego, Segundo (2015)
Objectives: To determine the frequency, admission diagnosis and case fatality rate of obstetrical/gynecological patients admitted to intensive care units (ICU). Design: Descriptive study. Setting: Department of Gynecology and Obstetrics and Intensive Care Units, Hospital Nacional Cayetano Heredia, Lima, Peru. Material: Medical records, ICU epicrisis and Perinatal Information System of all gynecological and obstetrical patients admitted to the ICU, from January 2008 through December 2009, were reviewed. Variables studied were maternal age, diagnosis at admission, ICU admission diagnosis, ICU stay, ICU interventions (mechanical ventilation, transfusions, inotropes use) and mortality. Main outcome measures: Outcome of patients admitted to UCI. Results: We analyzed 52 medical records representing 0,54 % of obstetrical interventions at the hospital. We reviewed 26 from year 2008, where age averaged 26,9 years; first cause of ICU admission was postpartum hemorrhage-related hypovolemic shock in 23% (n = 6), followed by severe preeclampsia, eclampsia, septic shock due to incomplete abortion, and peripartum myocardiopathy, 11,5% each (n = 3 each). In the 26 patients from year 2009, average age was 27 years; main causes for ICU admission were severe preeclampsia, eclampsia and septic shock due to infected abortion, 19,5% each (n= 5 each); postpartum hemorrhage-related hypovolemic shock and congenital heart disease represented 7,6% (n = 2 each). Mean hospitalization in ICU was 4 days in 2008 and 5,5 days in 2009, requiring mainly mechanical ventilation, fresh frozen plasma, and inotropic support. There were three deaths in 2008 and two in 2009. Conclusions: Postpartum hemorrhage-related hypovolemic shock and severe preeclampsia were the most frequent causes of admission to ICU. There were 5 deaths.